Soviet Security Operations Actions against Lithuanian Refugees in Germany in 1945–1950 - Juodis, Darius (Genocidas ir rezistencija, 2005)
The article analyses the attempts of the Soviet security to organise operations targeting the Lithuanian refugees many of who had settled on the German territory occupied by the Western allies. This study also gives concrete examples of the actions taken against Lithuanian émigré organisations and individuals. It reveals the aims of the NKGB (MGB) to conscript and infiltrate as many agents as possible into the group of emigrants in order to obtain valuable information. The article also reviews the activities of the Lithuanian SSR NKGB (MGB) division, the so-called Ber- lin operational group, as implemented in Germany. This operational group distinguished itself for its activities against the Lithuanian war refugees as well. This study emphasises that the NKGB (MGB) set as its task to gather various information about the Lithuanian emigration from different countries. Along with analysis of Soviet achievements in the area of intelligence, this article indicates the failures of the activities of the Soviet security. It discusses the reasons and highlights the drawbacks in gathering important reconnaissance information about the Lithuanian emigrants, and also the incompetence of individual officials which resulted in mistakes. The study points out that NKGB (MGB) put most of its efforts against the VLIK (Supreme Committee for Liberation of Lithuania), considered the most anti-Soviet organisation among the émigrés. Other political, cultural or scientific organisations would receive far less attention from Soviet security. Finally, the article reviews concrete operations of Soviet security agents against individual persons. Referring to specific instances, it describes arrests of people in Soviet-occupied Germany and the planned seizures in the other part of the country occupied by the Western allies.